Effects of carbapenems and their combination with amikacin on murine gut colonisation by Candida albicans. Issue 2 (8th June 2012) - Samonis, George; Galanakis, Emmanouil; Ntaoukakis, Markos; Sarchianaki, Emmanouela; Spathopoulou, Thomai; Dimopoulou, Dimitra; Kofteridis, Diamantis P.; Maraki, Sofia
Summary Carbapenems are broad‐spectrum antibiotics increasingly used for the treatment of severe infections. We evaluated the effects of four carbapenems given as monotherapies or in combination with amikacin on the level of gastrointestinal colonisation by Candida albicans in a previously established mouse model. Adult male Crl : CD1 (ICR) BR mice were fed chow containing C. albicans or regular chow. The mice fed with Candida chow had their gut colonised by the yeast. Both groups were subsequently given imipenem, meropenem, ertapenem, doripenem or their combination with amikacin or normal saline subcutaneously for 10 days. Stool cultures were performed immediately before, at the end and 1 week after discontinuation of treatment. Candida‐colonised mice treated with the antibiotics had higher counts of the yeast in their stools than control C. albicans‐colonised animals treated with saline. All four carbapenems and their combination with amikacin caused a significant increase in C. albicans concentration. Mice fed regular chow and treated with the study antibiotics or saline did not have any Candida in their stools. Dissemination of Candida was not detected in any animal. These data suggest that carbapenems and carbapenem plus amikacin induce substantial increases in the murine intestinal concentration of C. albicans.